Case studies in corporate strategies - Saptarshi, Dileep; Kochavara, Jairaj (Always learning., 2015)
The book traces the stories of ten Indian Companies which started out as small ventures and have grown into large corporations. They cover a wide spectrum of industry including steel, pharmaceuticals, alternate energy (engineering), information technology, FMCG, packaging, sugar, cut flower and, Food and Beverages. These companies cater to domestic as well as international markets and have resorted to exciting strategies to reach their pre-eminent positions. Moreover, the ten companies have faced difficult obstacles including global slowdowns and come out victorious.